Profil Siswa Terhadap Penguasaan Materi IPA Berdasarkan TesSoalTIMSS - Windri Yati; Arwin Achmad; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2017)
This study aims to determine the mastery of science material based on TIMSS test and internal factors in the form of learning motivation, learning habits, and students ability in answering question, and external factors that are parents education background. The sample in this reaserch was obtained from purposive sampling technique. The number of samples in this study were 105 students. Data collection techniques in this reaserch are TIMSS test, questionnaire, and interview of science subject teachers. The data analysis technique used to calculate the percentage that was interpreted into several category. The result indicates the student has enough categorize with the average (47,40). The external factors of the fathers educational background are categorized enough, and the internal factors of student learning habit are enough (52,71), the motivation to learn sience students categorized enough (60,10), and the abiity of students in answering the problem categorized enough (51,21)Tujuan penelitian untuk mengetahui penguasaan materi IPA berdasarkan tes soal TIMSS dan faktor internal berupa motivasi belajarIPA, kebiasaan belajar, dan kemampuan siswa dalam menjawab soal, serta faktor eksternal yaitu latar belakang pendidikan orang tua. Sampel yang digunakan berjumlah 105 siswa dipilih dengan purposive sampling. Data diperoleh dari tes soal TIMSS, angket, dan wawancara Guru matapelajaran IPA. Teknik analisis data yang digunakan yaitu menghitung persentase yang diinterpretasikan kedalam tabel kategori. Hasil penelitian menunjukkan bahwa tes soal TIMSS siswa berkategori cukupdengan rata-rata (47, 40). Faktor ekternal latar belakang pendidikan ayah yaitu berkategoricukup, dan faktor internal kebiasaan belajar siswa berkategori cukup (52,71), motivasi belajar IPA siswa berkategori cukup (60,10), dan kemampuan siswa dalam menjawab soal berkategori cukup (51,21).Kata kunci : faktor eksternal, faktor internal, IPA,TIMSS